Kelayakan Dan Praktikalitas Media Interaktif Petualangan Alfabet Berbasis Website Untuk Membaca Permulaan Pada Siswa Kelas 1 Sekolah Dasar - wahyu amirul; Muhardila Fauziah (Science and Education Journal (SICEDU), 2026)
This study aims to develop and determine the feasibility and practicality level of the “Petualangan Alfabet” website-based interactive media for beginning reading instruction in first-grade elementary school students. This research employed the Research and Development (R&D) method using the 4D development model, which consists of the define, design, develop, disseminate stages. The data were obtained through validation by material experts, media experts, and practitioners, as well as practicality testing through questionnaires of teacher and student responses and classroom observations.The results of the study indicate that the developed media has a very high level of feasibility, with validation scores of 90% from media experts, 86.25% from material experts, and 92% from practitioners, all categorized as highly valid. In addition, the practicality test results show that the media received very positive responses from both teachers and students, with an average percentage of 92% from teachers and 89% from students, categorized as highly practical.Based on these findings, the “Petualangan Alfabet” website-based interactive media is considered feasible and practical to be used as a learning medium to support beginning reading instruction for elementary school students.